Modelling trace metal transfer in large rivers under dynamic hydrology: A coupled hydrodynamic and chemical equilibrium model. (March 2017) - Garneau, Cyril; Sauvage, S.; Sánchez-Pérez, J.-M.; Lofts, S.; Brito, D.; Neves, R.; Probst, A.
Abstract: Trace metals (TMs) in rivers experience a complex chemistry that affects their partitioning between the dissolved and particulate fractions. Predictive modelling of this partitioning is challenging, particularly under variable hydrodynamic conditions in rivers. This paper presents a coupled hydrodynamic–geochemical model for trace metal dynamics in rivers, to highlight key parameters and set a basis for developing simplified models. A coupled model based on the hydrodynamic model MOHID and the chemical speciation model WHAM was applied to the middle part of the Garonne River (SW-France). The predictions of the coupled model are compared to those of a fixed Kd partitioning model. The model accurately simulates trace metal behaviour under varying hydrological conditions. The importance of the riverbed geomorphology and the diurnal variations in pH on TM concentrations in the water column are underlined. The sensitivity analysis ranked all physico-chemical parameters according to their influence on TM behaviour. Highlights: A hydrodynamic-geochemical model simulating trace metal (TM) in river was developed. TM behaviour was sensitive to the varying physico-chemistry of the water column. River morphology influenced the erosion and sedimentation zones of trace metals. The model suggested that diurnal cycle of pH strongly influences TM partitioning. Between 41 and 61% of Cu and 71–79% of Pb settled in the riverbed.